2014
DOI: 10.5194/isprsannals-ii-5-123-2014
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Appropriate Level of Detail (LoD) for a Building Information Model (BIM) – West Block, Parliament Hill, Ottawa, Canada

Abstract: ABSTRACT:In 2011, Public Works and Government Services Canada (PWGSC) embarked on a comprehensive rehabilitation of the historically significant West Block of Canada's Parliament Hill. With over 17 thousand square meters of floor space, the West Block is one of the largest projects of its kind in the world. As part of the rehabilitation, PWGSC is working with the Carleton Immersive Media Studio (CIMS) to develop a building information model (BIM) that can serve as maintenance and life-cycle management tool onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 11 publications
0
59
0
1
Order By: Relevance
“…at different LODs (Besuievsky, Barroso, Beckers, & Patow, 2014;Biljecki, Ledoux, & Stoter, 2017;Billger, Thuvander, & Wästberg, 2016;Brasebin, Perret, Mustière, & Weber, 2012;Deng, Cheng, & Anumba, 2016;Ellul, Adjrad, & Groves, 2016;Fai & Rafeiro, 2014;Neto, 2006;Peronato, Bonjour, Stoeckli, Rey, & Andersen, 2016;Strzalka, Monien, Koukofikis, & Eicker, 2015). In general, research has demonstrated that in certain spatial analyses the benefit of a finer LOD may be overestimated and even detrimental, as the potential small benefit may be countervailed by cost and complexity.…”
Section: Representation-induced Errormentioning
confidence: 99%
“…at different LODs (Besuievsky, Barroso, Beckers, & Patow, 2014;Biljecki, Ledoux, & Stoter, 2017;Billger, Thuvander, & Wästberg, 2016;Brasebin, Perret, Mustière, & Weber, 2012;Deng, Cheng, & Anumba, 2016;Ellul, Adjrad, & Groves, 2016;Fai & Rafeiro, 2014;Neto, 2006;Peronato, Bonjour, Stoeckli, Rey, & Andersen, 2016;Strzalka, Monien, Koukofikis, & Eicker, 2015). In general, research has demonstrated that in certain spatial analyses the benefit of a finer LOD may be overestimated and even detrimental, as the potential small benefit may be countervailed by cost and complexity.…”
Section: Representation-induced Errormentioning
confidence: 99%
“…In literature, some works show several steps in 3D HBIM modeling (Murphy et al, 2013); these workflows use different software with the necessary format conversion and we mainly observe a 2D simplification with slices of point clouds to build up the 3D model. In some work related to H-BIM, some samples of reconstruction of the existing condition have been described, often suggesting the generation of a semantic model based on a constant comparison between the information included in the historical treatises and the profiles achievable from a point cloud (Apollonio et al, 2013;De Luca et al, 2005;Fai et al, 2014). Others, instead, suggest the setting up of a library of historical building object models (H-BOM) that currently does not exist starting from the digital survey of an artifact (Quattrini et al, 2015) considering also the possibility to reuse the component Biagini et al, 2014;Santagati et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Because of the risk of high cost for analysis and BIM generation, LoD should not be specified at the beginning of the generative process, but defined and limited in time based on the needs and goals of the projects. It was agreed that the components of the BIM should be developed in such a way that LoD could be easily added or subtracted in the future for cases where the users may opt for more (heritage record) or less (facilities management) information ( Fai S., 2014). Fig.…”
Section: From Bim To Ma and Fea Automation In Modelingmentioning
confidence: 99%
“…The qualitative value of the l should not be defined a priori but gradually reached during its life cycle. The primary objective to achieve an appropriate 'as built' model should be determined according to the project purposes (Fai S., 2014).…”
Section: Level Of Detail (Lod) and Reverselod For Advanced Modelling mentioning
confidence: 99%
See 1 more Smart Citation